Analysis of Handover Trigger Scheme Based on Distance for LTE High-speed Railway Networks - Rui Zhang; Muqing Wu; Yifan Zhang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
In high-speed railway environment, frequent handovers and high handover failure probability result in serious communication interruptions and call drops, which become pressing problem to be solved. Alternative reference point based handover scheme can be an applicative solution for high-speed rail. This paper analyzes the impact of handover location on the handover performance. And numerical analysis is utilized to give a method to determine the distance from the serving eNodeB and the adjacent one to the mobile terminal when handover is triggered. Handover failure probability is used as criteria for performance. Simulation results show that the proposed scheme has a better performance than typical event based scheme in high speed environment.